1991
DOI: 10.1007/bf00293459
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin-immunoreactive neurons in the human central nervous system are decreased in Alzheimer's disease

Abstract: Immunohistochemical localization of the Ca(2+)-binding protein parvalbumin (PV) was investigated in the adult human central nervous system (CNS). The antiserum against purified rat skeletal muscle PV specifically recognized certain neuronal populations and their processes. Strongly positive were Purkinje, basket and stellate cells of the cerebellum, cerebral cortical nonpyramidal cells, and neurons in the thalamic reticular and ventrolateral nuclei, subthalamic nucleus, lateral and medial geniculate bodies, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 39 publications
2
31
1
Order By: Relevance
“…Receptor binding for GABA was significantly reduced in the FC of AD brains compared to controls with no significant alterations in the hippocampus [27,28,29]. In addition, a decrease in parvalbumin-immunoreactive cortical pyramidal neurons was reported [30]. However, other studies showed a relative resistance of these cells [31,32] and the presence of parvalbumin-immunoreactive abnormal neuritis and aberrant sprouts [33].…”
Section: Discussionmentioning
confidence: 97%
“…Receptor binding for GABA was significantly reduced in the FC of AD brains compared to controls with no significant alterations in the hippocampus [27,28,29]. In addition, a decrease in parvalbumin-immunoreactive cortical pyramidal neurons was reported [30]. However, other studies showed a relative resistance of these cells [31,32] and the presence of parvalbumin-immunoreactive abnormal neuritis and aberrant sprouts [33].…”
Section: Discussionmentioning
confidence: 97%
“…Changes in morphology, density, and size of PV-immunoreactive neurons, associated with neurodegenerative disease and aging, have been reported in brains of the rat, hamster, and human (Seto-Ohshima et al 1988;Seki and Arai 1995;de Jong et al 1996). No significant changes of PV-immunoreactive neurons have been described in the cerebellar cortex of humans or the cerebellum and reticular thalamic nucleus of the hamster (Satoh et al 1991;Lolova and Davidoff 1992). However, a loss of PV-immunoreactive neurons has been reported in the normal aged hippocampus and olfactory bulb (Seki and Arai 1995;Hwang et al 2003).…”
Section: Age-related Changes Of Cabpsmentioning
confidence: 93%
“…The present data were taken from an animal 21 years of age [owl monkeys reportedly live to more than 27 years of age; Nowak, 1999]. However, various studies have demonstrated that there is no decrease in the number of inhibitory interneurons and their axon terminals in the normal aging brain [Ichimiya et al, 1988;Hof and Morrison, 1991;Satoh et al, 1991;Leuba et al, 1998]. …”
Section: Methodological Limitations: Animal and Areas Included For Studymentioning
confidence: 99%